ADJUVANT GOSERELIN IN PRE-MENOPAUSAL PATIENTS WITH EARLY BREAST CANCER: RESULTS FROM THE ZIPP STUDY - M. Baum; A. Hackshaw; J. Houghtona; L. E. Rutqvist; T. Fornander; B. Nordenskjold; A. Nicolucci; R. Sainsburya (ABV-press, 2014)
The Zoladex In Pre-menopausal Patients (ZIPP) study was designed to determine whether addition of goserelin ('Zoladex') and/or tamoxifen to adjuvant therapy (radiotherapy and/or chemotherapy), provided benefit to pre- or peri-menopausal women with operable, early breast cancer.